Geochemical Modeling of Celestite (SrSO4) Precipitation and Reactive Transport in Shales - Esteves, Barbara F; Spielman-Sun, Eleanor; Li, Qingyun; Jew, Adam D; Bargar, John R; Druhan, Jennifer L (Environmental science & technology, 2022)
Celestite (SrSO4) precipitation is a prevalent example of secondary sulfate mineral scaling issues in hydraulic fracturing systems, particularly in basins where large concentrations of naturally occurring strontium are present. Here, we present a validated and flexible geochemical model capable of predicting celestite formation under such unconventional environments. Simulations were built using CrunchFlow and guided by experimental data derived from batch reactors. These data allowed the constraint of key kinetic and thermodynamic parameters for celestite precipitation under relevant synthetic hydraulic fracturing fluid conditions. Effects of ionic strength, saturation index, and the presence of additives were considered in the combined experimental and modeling construction. This geochemical model was then expanded into a more complex system where interactions between hydraulic fracturing fluids and shale rocks were allowed to occur subject to diffusive transport. We find that the carbonate content of a given shale and the presence of persulfate breaker in the system strongly impact the location and extent of celestite formation. The results of this study provide a novel multicomponent reactive transport model that may be used to guide future experimental design in the pursuit of celestite and other sulfate mineral scale mitigation under extreme conditions typical of hydraulic fracturing in shale formations.